Bioactivity of Thyroid Hormone Analogs at Cancer Cells - Davis, Paul J.; Tang, Heng-Yuan; Hercbergs, Aleck; Lin, Hung-Yun; Keating, Kelly A.; Mousa, Shaker A. (Frontiers in Endocrinology, 2018)
In the context of genomic thyroid hormone actions in normal (noncancer) cells that involve primary interactions of with nuclear thyroid hormone receptors (TRs), L-thyroxine (T4) and 3,3’,5-triiodo-L-thyronine (reverse T3, rT3) have little bioactivity. In terms of TRs, T4 is a prohormone from which the active nuclear ligand, 3,3’,5’-triido-L-thyronine (T3), is generated by deiodination. Deaminated T4 and T3 metabolites have different genomic effects: tetraiodothyroacetic acid (tetrac) is a low grade thyromimetic derivative of T4, whereas triiodothyroacetic acid (triac) , the acetic acid metabolite of T3, has substantial thyromimetic activity. In cancer cells, In terms of genomic effects, tetraiodothyroacetic acid (tetrac) is a low-grade thyromimetic derivative of T4, but triiodothyroacetic acid (triac), the acetic acid metabolite of T3, has substantial thyromimetic activity. tThe cell surface receptor for thyroid hormone on integrin αvβ3 mediates nongenomic actions of thyroid hormone analogues. The integrin is expressed in large measure by cancer cells and dividing endothelial cells and has a substantially different panel of responses to thyroid hormone analogues. At αvβ3, T4 is a potent proliferative, anti-apoptotic and pro-angiogenic hormone and is the primary ligand. rT3 may also be proliferative at this site. In contrast, tetrac and triac are antagonists of T4 at αvβ3, but also have anticancer properties at this site that are independent of their effects on the binding of T4.